Economic valuation of the impact of sand washing in Boncong, Tuban Regency, East Java, Indonesia - Nikmah, Lailatul; Ramadhani, Adifa Putri; Khoirunnisa, Rana; Maghfiiroh, Tanya Bunga (Journal of Marine Resources and Coastal Management, 2022)
Bancar District is one of the strategic areas in the Tuban Regency Spatial Plan i.e. as the Minapolitan strategic area. Since 2019, in the Bancar District area, precisely in Boncong Village, there has been a silica sand washing area which its waste directly dumped into the river and resulted in many negative impacts. This study aims to calculating the environmental cost due to sand washing activity in Boncong area. The environmental cost in this study was calculated through cost based approach. The results of the study show that the losses incurred due to silica sand washing activity in Boncong reach IDR 508,600,000.00 per year, i.e. IDR 496,000,000.00 per year for maintenance of fisher’s ship and additional costs for aquaculture water treatment are IDR 12,600,000.00 per year. Economic approach, and also an ecological approach, has potentially large implications for policy-making of mitigation the impact of sand washing activity.